Proceedings of the Third Linguistic Annotation Workshop on - ACL-IJCNLP '09 2009
DOI: 10.3115/1698381.1698384
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the benefits of partial automatic pre-labeling for frame-semantic annotation

Abstract: In this paper, we present the results of an experiment in which we assess the usefulness of partial semi-automatic annotation for frame labeling. While we found no conclusive evidence that it can speed up human annotation, automatic pre-annotation does increase its overall quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Inaccurate pre-annotations may require deletion or correction, and evidence indicates that time-savings correlate with preannotation accuracy. 25 26 For some tasks, pre-annotation may not alter annotation time, 27 and the presence of multiple, inaccurate pre-annotations may instead increase annotation time. 25 28 Also, pretrained systems capable of pre-annotating for a specific task or medical realm either may not exist or may not be sufficiently accurate when used within a new domain.…”
Section: Introductionmentioning
confidence: 99%
“…Inaccurate pre-annotations may require deletion or correction, and evidence indicates that time-savings correlate with preannotation accuracy. 25 26 For some tasks, pre-annotation may not alter annotation time, 27 and the presence of multiple, inaccurate pre-annotations may instead increase annotation time. 25 28 Also, pretrained systems capable of pre-annotating for a specific task or medical realm either may not exist or may not be sufficiently accurate when used within a new domain.…”
Section: Introductionmentioning
confidence: 99%
“…Once each annotator has annotated half of the corpus, pre-annotation has been applied, as a proven way to obtain significant gains in both annotation time and quality of annotation [Fort and Sagot, 2010;Marcus et al, 1993;Rehbein et al, 2009]. Since we were targeting errors of omission (segments missed by the annotators), an "overly-general" CRF model was trained on all 300 documents, and applied on the corpus.…”
Section: Methodsmentioning
confidence: 99%
“…Rehbein et al [31] performed quite thorough experiments in the field of semantic frame assignment annotation. Although in this case, the results of the experiments are a bit disappointing as they could not find a direct improvement of annotation time using pre-annotation, they found that noisy and low-quality pre-annotation does not overall corrupt human judgment.…”
Section: Pre-annotation Techniquementioning
confidence: 99%